Ready access to densely substituted furans using Tsuji-Wacker type cyclization - Masal, Dattatraya P.; Choudhury, Rahul; Singh, Aman; Reddy, D. Srinivasa (Journal of Organic Chemistry, 2022)
A competent method for the construction of highly substituted furans catalyzed by Pd(II) and Cu(II) chloride has been developed. The method provides easy access to di-, tri-, and tetrasubstituted furans from corresponding diols with relatively mild conditions in a unified strategy. The developed method has been successfully tested with more than 25 substrates, which resulted in furans of multiple substitution patterns with up to 84% isolated yields.

Identification of new modulator of DNA repairing pathways based on natural product (±)-peharmaline A - Kulkarni, Akshay S.; Dash, Anshurekha; Shingare, Rahul D.; Chand, Jagdish; Manhas, Diksha; Singh, Aman; Nandi, Utpal; Goswami, Anindya; Reddy, D. Srinivasa (Bioorganic & Medicinal Chemistry, 2023)
The complex heterogenic environment of tumour mass often leads to drug resistance and facilitate chemo insensitivity triggering more malignant phenotypes among cancer patients. Major DNA-damaging cancer drugs have been consistently proven unsuccessful in terms of elevating chemo-resistance. (& PLUSMN;)-peharmaline A, a hybrid natural product isolated from seeds of Peganum harmala L. possesses significant cytotoxic activities. Herein, we have described the design, and synthesis of a novel library of close and simplified analogues around the anticancer natural product (& PLUSMN;)-peharmaline A and investigated their cytotoxic activities, which led to the identification of three structurally simplified lead compounds exhibiting better potency than parent natural product. Among them, demethoxy analogue of peharmaline A was further investigated for its anticancer potential eliciting demethoxy analogue as potent DNA-damage inducing agent attenuating the expression of the proteins responsible for the DNA damage repair. Therefore, this demethoxy analogue warrants detailed investigations for the confirmations of the molecular mechanism-based studies responsible for its anticancer activity.
Keywords: DNA damage; EMT; Pictet; Spengler reaction; Structure-activity relationship; Total synthesis